Effects of Dance Movement Therapy and Other Dance-Based Interventions on Depressive Disorders - Ptak, Anita; Szyc, Michał (Journal of Education, Health and Sport, 2024)
Introduction: Depression is a medical condition affecting hundreds of millions of people worldwide. It can affect different age groups, both children and the elderly. The principal treatments for depression are pharmacotherapy based mainly on SSRIs and SNRIs and psychotherapy (e.g. cognitive-behavioural). Researchers are looking for interventions that can support the treatment of depressive disorders and complement primary therapy. One of the issues being explored is the impact of Dance Movement Therapy and other dance- based interventions on depressive symptoms and general well-being. Aim of the study: Analysis of the available research on the effects of Dance Movement Therapy and other dance- based interventions on depressive symptoms and general psychological well-being including anxiety and stress symptoms. Methods: Review of the available literature available in the scientific databases PubMed and Google Scholar by searching with key words such as: dance movement therapy, dance, depression, depressive disorders, stress. In addition, a review of specialised literature from the field of psychiatry was performed. Conclusion: According to the available data, the introduction of DMT or other forms of dance generally has positive effects, alleviating depressive symptoms in many study groups. In some trials, a reduction in anxiety and stress was also noted among those who underwent the intervention. The best effects of the therapy have been found among people with mild depression. The effects among people with severe depression are not as clear. The inclusion of dance in people with depressive disorders is likely to be a good intervention in patients with mild depressive symptoms and can be used as an adjunctive therapy to appropriate psychiatric treatment. The positive effects of DMT and dance on the wellbeing of cancer patients have also been noted.